2018
DOI: 10.1080/24740527.2018.1451251
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to postoperative pain management in Rwanda from the perspective of health care providers: A contextualization of the theory of planned behavior

Abstract: Methods: The theory of planned behavior (TPB) guided development of a questionnaire to measure intent to assess and treat postoperative pain. Focus groups and individual interviews were used to contextualize the final questionnaire and generate questions related to pain management practice. Health care providers from two Rwandan teaching hospitals involved in postoperative pain management completed the TPB questionnaire in May 2015. TPB subscale scores were analyzed to identify demographic and practice charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…However, patients were very comfortable throughout the interview and which might neutralize the possible bias. By using purposive and maximum variation sampling to include a diverse group of participants, however, we may have counteracted this limitation, as indicated by the fact that our findings are in line with previous reports [ 45 , 47 ]. Nevertheless, we cannot guarantee that by using these sampling techniques we included a wide enough variety of people to obtain information on all relevant barriers to and facilitators of QPM, i.e.…”
Section: Limitationssupporting
confidence: 66%
See 1 more Smart Citation
“…However, patients were very comfortable throughout the interview and which might neutralize the possible bias. By using purposive and maximum variation sampling to include a diverse group of participants, however, we may have counteracted this limitation, as indicated by the fact that our findings are in line with previous reports [ 45 , 47 ]. Nevertheless, we cannot guarantee that by using these sampling techniques we included a wide enough variety of people to obtain information on all relevant barriers to and facilitators of QPM, i.e.…”
Section: Limitationssupporting
confidence: 66%
“…In addition, resource-based limitations, such as the lack of strong analgesics like opioids, prevents HCPs from delivering QPM. A very recent report from Rwanda also stated that the lack of resources was the most frequently identified barrier to adequate treatment of postoperative pain [ 47 ]. In Africa, a lack of resources has prevented the health care system from delivering QPM for several years [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…DOI: https://dx.doi.org/10.17352/ojpm.000023 [6]. Developing countries remain to face this impacts with establishing and maintaining effective programs for the enhancement of POP [8,9]. In Africa, the issue of pain has been visited principally in relative to AIDS and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This lead to many complications such as anxiety and sleep disturbance and increase patient stay in hospital 4 . Despite of persistent work done on pain management and introduction of advance therapies only slight improvements have been achieved and still 45.6 % of the patients reported pain in early stage of cancer while 73.9 % of the patients reported severe pain in advanced stage of cancer in many settings 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Oncology nurses are considered to have an obvious role in managing the pain of patients suffering from cancer. However, It is observed that nurses face multiple factors as barriers that cause them to inefficiently participate in assessment and management of pain [5][6][7] . These barriers are lack of pain management specialists in the health care team, improper nurse to patient ratio, religious and cultural misconception about the cancer pain 8 .…”
Section: Introductionmentioning
confidence: 99%